MASS VACCINTION IN RURAL AREA OF IRAN: A SEROEVALUATION - K. Nasseri; H. Malekafzali; M.Semsar-yazdi; P. Parvaz (Tehran University of Medical Sciences, 1983)
In an attempt to convert mass vaccination practices to the Extended Programme on Immunization, a sero-evaluation study was carried out in rural Iran in 1976. A total of 22 246 rural children of 2-12 years of age were sampled. Blood samples taken on filter paper were tested by indirect hemagglutination technique to determine the level of circulating antibodies against tetanus toxoid. Tetanus was selected as an index not only because natural antibody against it is practically non existent, but also because protective levels of this antibody can reveal vaccination status of the individuals. Results show that except for few districts where complete protection reaches over 70%, the immunization status is not commendable. Moreover, no specific pattern for immunization could be detected. These and other results are discussed.